Personality correlates of intimate partner violence subtypes: A latent class analysis. Issue 4 (12th March 2018) - Cascardi, Michele; Chesin, Megan; Kammen, Molly
Abstract : Perpetrators of intimate partner violence (IPV) represent a heterogeneous group who engage in a variety of aggressive acts which often co‐occur. However, few studies take this co‐occurrence into consideration. Failure to consider overlapping forms of IPV confounds understanding of risk factors for physical IPV, which in turn undermines identification, prevention, and intervention efforts. Though rarely studied in emerging adults, personality variables have recently been identified as important correlates of IPV. The primary aims of the current studies are to identify distinct subgroups of moderate and severe psychological and physical IPV and personality covariates of class membership. Two studies were conducted at different public regional universities in the northeast ( n = 500; n = 497). Both samples were about two‐thirds female, approximately one‐half White, one‐fifth Black, and one‐quarter Latino, of any race. Latent Class Analysis identified three subgroups in both studies: low, moderate, and severe IPV. The severe and moderate IPV groups included those who reported threats and moderate physical IPV while the severe IPV group also included those who engaged in severe and injurious forms of physical IPV. Multinomial regression analysis showed that impulsive aggression discriminated moderate and severe from low IPV (Study 1), and more frequent emotionally abusive and controlling behavior, a hostile‐dominant interpersonal style and trait aggression discriminated among all three groups, with severe IPV having the greatest likelihood of controlling behavior and aggression (Study 2). IPV is represented by distinct subgroups that vary by severity of IPV with different personality covariates. General aggressive and domineering tendencies in relationships characterize those engaging in severe IPV.